A structural study of gallstones. Issue 8 (August 1975) - Bills, P M; Lewis, D
Abstract : A number of gallstones have been studied using methods which have not previously been applied to gallstones. In particular, the use of scanning electron microscopy and micro-x-radiography have allowed detailed observations to be made on the structure of the stones and the distribution of the various components within the stones. Large differences in structure have been shown to exist between stones having similar overall chemical compositions. In cholesterol gallstones containing calcium carbonate the crystalline nature, distribution and method of deposition of the calcium carbonate was studied and was found to vary from stone to stone. Evidence was found for the presence of fibrous material in the centre of many stones and it is possible that this material acted as a nucleus for the deposition of the other stone components.